Pengaruh Tayangan Program Tonight Show di NET TV terhadap Minat Menonton: Survey pada Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Jakarta Angkatan 2019 - Ilham Aryasatya; Mulkan Habibi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Television media is an efficient media in reaching a very large number of communicants and relatively far away places. The Tonight Show program is a talk show program that aims to provide information and entertainment to the public. This study aims to measure the influence of the "Tonight Show" program on NET TV on the viewing interest of Communication Science students at the University of Muhammadiyah Jakarta class of 2019. This study uses several theories, namely the variable (X) Program theory and the variable (Y) Viewing Interest theory. This study uses a survey method with a quantitative approach to measure the influence of students who watch the Tonight Show program on Net TV. From the results of this study, the t-count value was obtained 8.3666> t-table 1.667, so Ho was rejected and H1. So that the results obtained that there is a significant influence between the influence of the Tonight Show Program on Viewing Interest. In addition, based on the correlation value R shows that the influence of the Tonight Show Program (X) on the viewing interest (Y) of Communication Science students at the University of Muhammadiyah Jakarta has a very strong and significant R 0.985. Meanwhile, the Adjusted Rsquare value is 0.970, which means that the influence of the independent variable (X) on the dependent variable (Y) is 97%, while the remaining 3% is influenced by other factors unknown in this study.customers.